A new performance-based measure of children's socioemotional understanding: Psychometric properties of the domino test for socioemotional understanding (DOTSEMU). Issue 6 (2nd November 2019) - Papieska, Joanna; Spilt, Jantine L.; Laevers, Ferre
ABSTRACT: The main goal of this study was to investigate the psychometric properties of a newly-developed performance-based test of socioemotional understanding: the Domino Test for Socioemotional Understanding (DOT SEMU ). The sample consisted of 304 third-graders from 8 to 10 years ( Mage = 9.31, SD = 0.44, 50% boys) from six Polish primary schools (sixteen classes). The data was collected using teacher and parent questionnaires (on pro-social behavior, hyperactivity, emotional problems, peer problems, and conduct problems), peer nominations of cooperative behavior, and performance-based tests of social understanding and emotional awareness. Results suggested that the reliability of the DOT SEMU was modest. The DOT SEMU explained unique variance in children's outcomes, taking into account another validated and performance-based measure of emotional awareness. Overall, the study provided first evidence that the DOT SEMU assesses socioemotional understanding and contributes to the prediction of socio-behavioral and emotional (mal)adjustment in children.